ORGANIZATIONAL IDENTIFICATION AND PERSONAL PROACTIVITY IN WORK GROUPS: A STRUCTURAL EQUATIONS MODEL - Topa Cantisano, Gabriela; Morales Domínguez, Francisco (Anales de Psicología / Annals of Psychology, 2006)
The present study explores the relationships between organizational identification and both citizenship behavior and personal initiative within work groups. A sample of 336 employees was used to test the adjustment of different causal models to the data. Structural equations analyses showed that organizational identification predicts outcomes regarding employees’ organizational citizenship behaviors and personal initiative, but this relation was partially mediated by group cohesion.